Anti-ulcerogenic Activity of the Fractions of Methanol Leaves Extract of Hannoa Klaineana in Wistar Rats - Ibrahim Abubakar; Hassan Yankuzo Muhammad; Yushau Baraya Shuaibu; Muazu Gusau Abubakar; Sanusi Wara Hassan (International Journal of Pharma and Bio Sciences, 2021)
Nowadays, search for medicinal plants with anti-ulcerogenic activity has been increased due to their negligible side effects compared to synthetic drugs. Hannoa klaineana Pierre & Engl. is used in traditional medicine for the treatment of cancer, malaria, fever, pain and diverse gastrointestinal disorders including peptic ulcer diseases (PUDs). The present study was conducted to evaluate anti-ulcerogenic activity of n-hexane, ethylacetate and butanol fractions of the Hannoa klaineana leaves and to elucidate mechanism of anti-ulcerogenic activity of the most active fraction. Anti-ulcerogenic activities of n-hexane, ethylacetate and butanol fractions (400 mg/kg b.wt) were evaluated using ethanol-induced gastric ulcer model. Mechanism of anti-ulcerogenic activity of the most active fraction (100, 200 and 400 mg/kg b.wt) was elucidated using HCl/ethanol-induced gastric ulcer model. The principal compounds in the active fraction were isolated using column chromatography, thin layer chromatography (TLC) and preparative TLC. Ethylacetate fraction (EAF) had the highest anti-ulcerogenic activity with protective effect of 99.82% against gastric damage. EAF also exhibited a significant (p<0.05) decrease in mean ulcer index, with protective effect of 99.54% against HCl/ethanol-induced gastric lesions at 400 mg/kg. Increase of gastric mucus content (p<0.05) and pH of gastric juice in the rats pre-treated with EAF (100, 200 and 400 mg/kg) were observed. The EAF significantly (p<0.05) decreased levels of malondialdehyde (MDA) coupled with significant increase (p<0.05) in the levels of superoxide dismutase (SOD) and catalase (CAT) in the gastric mucosal homogenates. The most active EAF has high phenolic and total flavonoid content. At 500 g/ml, the EAF showed maximum DPPH inhibition of 89.10% comparable to that of ascorbic acid (92.00%). Ethylacetate is the most active fraction of Hannoa klaineana leaves and its mechanism of action could be attributed to inhibition of lipid peroxidation by enhancing antioxidant potential of the gastric mucosa leading to gastroprotection.